Early Diagnosis of Fragile X Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Surveys from 274 families with at least one child with fragile X syndrome (FXS) were used to determine factors associated with the discovery of the diagnosis in a study at the University of North Carolina, Chapel Hill, NC.